TIDE AND TIDAL CURRENT IN THE BALI STRAIT, INDONESIA - Berlianty, Dessy; Yanagi, Tetsuo (Marine Research in Indonesia, 2011)
Tide and tidal current model of the Bali Strait in Indonesia is produced by using a Coupled Hydrodynamical-Ecological Model for Regional and Shelf Seas (COHERENS). With its resolutions in the horizontal (500meters) and the vertical (4layers), the model well reproduces the four major tidal constituents, namely M2, S2, K1, and O1 tides, and their currents. Furthermore the model is used to investigate the tide-induced residual flow and tidal front in the Bali Strait. As a results, the tide-induced residual flow in the Bali Strait during the spring tide on May 16th in 2010 can be attributed to the variation of the strength of two eddies. The first one is the clockwise circulation in the shallow area at the wide part of the strait, while the second one is the small clockwise circulation in the south of the narrow strait. On the other hand, as suggestion from Simpson and Hunter (1974), the tidal front is determined by the value of log(H/U3) (where is the water depth in meters and the amplitude oftidal current amplitude in ms-1). The front detected by the image of sea surface temperature distribution from the satellite corresponds with the contour log(H/U3) of 6.5.